Instructional Practices and Holistic Learner Development in Elementary Education: Educational Perspectives from the San Isidro District, Isabela - Bascos, Teddy Joy; GONZALES, ALMA (Azal Arts and Humanities, 2026)
Holistic learner development has become a significant educational priority in elementary education as schools increasingly recognize the importance of nurturing learners’ cognitive, emotional, social, moral, and behavioral growth alongside academic achievement. This qualitative phenomenological study explored teachers’ instructional practices and their perceived contributions to holistic learner development in elementary education within the San Isidro District, Isabela. The study involved twelve public elementary school teachers purposively selected based on their teaching experience and active engagement in learner-centered instructional practices. Data were gathered through semi-structured interviews, classroom observations, and document analysis. Using Braun and Clarke’s thematic analysis, the findings revealed five major themes: (1) Learner-Centered and Contextualized Instructional Practices; (2) Cultivating Social and Emotional Development Through Classroom Interaction; (3) Values Formation and Character Development Through Integrative Teaching Practices; (4) Collaborative Learning and Inclusive Classroom Participation; and (5) Instructional and Contextual Challenges Affecting Holistic Learner Development. Teachers emphasized that differentiated instruction, experiential learning activities, collaborative tasks, contextualized lessons, and values integration positively influenced learners’ academic engagement, emotional growth, social interaction, and self-confidence. Participants also highlighted challenges related to limited instructional resources, learner diversity, parental involvement, and instructional workload. The study concludes that holistic learner development is strengthened through responsive, inclusive, and learner-centered instructional practices supported by collaborative educational environments. The findings provide implications for teacher professional development, curriculum enhancement, and educational policy focusing on holistic and inclusive elementary education. Introduction Elementary education serves as a foundational stage in shaping learners’ academic competence, social behavior, emotional well-being, moral values, and overall personality development. In contemporary educational contexts, schools are increasingly expected not only to promote academic achievement but also to nurture learners’ holistic growth and lifelong competencies. Holistic learner development refers to the balanced cultivation of learners’ intellectual, emotional, social, physical, moral, and behavioral dimensions to prepare them for meaningful participation in society. Within Philippine basic education, holistic development has become an essential goal aligned with learner-centered and inclusive educational frameworks. Educational reforms emphasize the importance of developing well-rounded learners equipped with critical thinking skills, emotional resilience, collaborative competencies, moral values, and social responsibility. Teachers therefore play a critical role in implementing instructional practices that support both academic and non-academic learner outcomes. Instructional practices such as differentiated instruction, collaborative learning, experiential activities, contextualized teaching, reflective learning tasks, and values integration have increasingly been recognized as effective approaches in promoting holistic learner development. These practices provide learners with meaningful learning experiences that encourage active participation, self-expression, social interaction, and emotional engagement. Previous studies suggest that learner-centered and inclusive instructional approaches positively influence learners’ academic motivation, emotional well-being, classroom participation, and interpersonal skills (Florian & Black-Hawkins, 2011; Gay, 2018). Experiential and contextualized learning activities also contribute to deeper learner understanding and social-emotional growth by connecting instructional content to real-life experiences. Despite the recognized importance of holistic education, teachers continue to encounter challenges related to resource limitations, learner diversity, classroom management, parental involvement, and instructional demands. Furthermore, limited qualitative studies have explored teachers’ lived experiences and educational perspectives regarding instructional practices that support holistic learner development in elementary education settings. Thus, this study explored instructional practices and holistic learner development in elementary education from the educational perspectives of teachers in the San Isidro District, Isabela. Review of Related Literature 2.1 Holistic Learner Development in Elementary Education Holistic learner development emphasizes the balanced growth of learners’ intellectual, emotional, social, moral, and behavioral dimensions. According to Miller (2019), holistic education recognizes learners as multidimensional individuals whose educational experiences should support academic achievement alongside personal and social development. Holistic educational approaches promote emotional well-being, empathy, collaboration, creativity, self-awareness, and responsible decision-making. Schools therefore serve as environments that nurture both cognitive and socio-emotional competencies necessary for lifelong learning and responsible citizenship. 2.2 Learner-Centered Instructional Practices Learner-centered instruction focuses on active participation, differentiated learning opportunities, and meaningful learner engagement. Teachers facilitate learning experiences that accommodate learners’ diverse backgrounds, interests, abilities, and learning styles. According to Weimer (2018), learner-centered teaching encourages autonomy, collaboration, critical thinking, and reflective learning. Differentiated instruction and experiential learning activities also strengthen learner motivation and participation. 2.3 Social and Emotional Learning in Classroom Instruction Social and emotional learning (SEL) involves the development of learners’ self-awareness, emotional regulation, interpersonal skills, empathy, and responsible decision-making. Research indicates that positive classroom relationships and supportive learning environments significantly contribute to learners’ emotional well-being and academic success (CASEL, 2020). Teachers play an important role in fostering respectful classroom interactions, collaborative learning opportunities, and emotionally supportive educational environments. 2.4 Inclusive and Contextualized Education Inclusive education emphasizes equitable participation and meaningful learning opportunities for all learners regardless of their backgrounds, abilities, or learning needs. Contextualized teaching further enhances learner understanding by connecting lessons to learners’ experiences and local realities. Gay (2018) emphasized that culturally responsive and contextualized instructional practices improve learner engagement, participation, and self-confidence in classroom learning. Methodology This study utilized a qualitative phenomenological research design to explore teachers’ instructional practices and their perceived contributions to holistic learner development in elementary education. Phenomenology was appropriate because it enabled the researchers to understand participants’ lived experiences, instructional approaches, and educational perspectives within authentic classroom contexts. The study was conducted in selected public elementary schools in the San Isidro District, Isabela. The participants consisted of twelve public elementary school teachers selected through purposive sampling. Participants were required to have at least three years of teaching experience and active involvement in learner-centered instructional practices. Data were gathered through semi-structured interviews, classroom observations, and document analysis involving lesson plans, instructional materials, and classroom activity records. Data were analyzed using Braun and Clarke’s (2006) thematic analysis involving coding, theme generation, theme review, and thematic interpretation. Credibility was established through member checking and triangulation, while dependability, confirmability, and transferability were ensured through audit trails, reflective journaling, and thick descriptions of participants’ instructional experiences. Results and Findings Theme 1: Learner-Centered and Contextualized Instructional Practices Participants emphasized the importance of learner-centered and contextualized instructional approaches in promoting meaningful learning experiences and holistic learner development. Teachers described utilizing differentiated instruction, experiential activities, localized examples, and interactive learning tasks to sustain learner participation and understanding. One participant shared: “Mas natututo ang learners kapag relatable at connected sa kanilang experiences ang lessons.” Another teacher explained: “I adjust my teaching strategies depending on the learners’ needs and abilities.” Teachers observed that contextualized instruction increased learners’ engagement, confidence, and classroom participation. Participants also emphasized that experiential and collaborative activities helped learners become more active, independent, and reflective learners. The findings indicate that learner-centered and contextualized instructional practices positively support learners’ academic, emotional, and social development. Theme 2: Cultivating Social and Emotional Development Through Classroom Interaction Participants highlighted the importance of positive classroom relationships and interactive learning environments in supporting learners’ emotional and social development. One participant stated: “Kapag supportive ang classroom environment, mas confident mag-express ang learners.” Another teacher shared: “Collaborative activities help learners develop respect and teamwork.” Teachers observed that classroom discussions, peer interaction, cooperative learning tasks, and reflective activities strengthened learners’ communication skills, empathy, emotional regulation, and self-confidence. Participants further explained that emotionally supportive classrooms encouraged learners to participate actively without fear of embarrassment or criticism. The findings suggest that instructional practices promoting positive social interaction contribute significantly to holistic learner development. Theme 3: Values Formation and Character Development Through Integrative Teaching Practices Teachers emphasized the integration of values education and character formation within classroom instruction. Participants explained that instructional activities often incorporated lessons on respect, responsibility, discipline, empathy, cooperation, and honesty. One participant remarked: “Hindi lang academics ang importante kundi pati values at magandang asal.” Another teacher explained: “We integrate values formation in classroom discussions and activities.” Teachers observed that integrating moral and behavioral development into daily instruction positively influenced learners’ attitudes, classroom behavior, and interpersonal relationships. The findings highlight the role of instructional practices in supporting learners’ moral and character development alongside academic growth. Theme 4: Collaborative Learning and Inclusive Classroom Participation Participants described collaborative learning and inclusive classroom participation as essential components of holistic learner development. One participant shared: “Group activities encourage learners to help and learn from each other.” Another teacher explained: “Inclusive classroom practices help learners feel accepted and valued.” Teachers emphasized that collaborative and inclusive instructional approaches strengthened learners’ social interaction, communication skills, confidence, and participation regardless of ability levels. Participants also observed that inclusive practices reduced learners’ anxiety and promoted positive peer relationships within the classroom. The findings indicate that collaborative and inclusive instructional environments contribute to learners’ social-emotional growth and classroom engagement. Theme 5: Instructional and Contextual Challenges Affecting Holistic Learner Development Despite positive instructional practices, participants encountered several challenges affecting holistic learner development. One participant shared: “Minsan mahirap ma-address lahat ng learner needs dahil sa dami ng pupils.” Another teacher stated: “Limited resources affect the implementation of interactive activities.” Participants emphasized the need for institutional support, professional development opportunities, and collaborative stakeholder participation to strengthen holistic educational practices. Discussion The findings demonstrate that learner-centered, contextualized, and inclusive instructional practices positively influence holistic learner development in elementary education. Through differentiated instruction, collaborative learning, experiential activities, and values integration, teachers support learners’ academic achievement alongside emotional, social, and moral growth. The study further revealed that positive classroom relationships and supportive learning environments strengthen learners’ confidence, communication skills, empathy, and classroom participation. Collaborative and inclusive practices likewise contribute to social-emotional development and positive peer interaction. However, the successful promotion of holistic learner development requires adequate instructional resources, teacher preparedness, parental involvement, and institutional support systems. The identified challenges indicate the importance of strengthening educational support mechanisms and professional development initiatives focusing on inclusive and holistic instructional practices. Conclusion Holistic learner development in elementary education is strengthened through learner-centered, contextualized, collaborative, and inclusive instructional practices. Teachers play a crucial role in nurturing learners’ academic competence, emotional well-being, social interaction, and moral development through meaningful classroom experiences and supportive educational environments. Despite instructional and contextual challenges, teachers continue to implement responsive and values-oriented pedagogical practices that contribute to balanced learner growth. Educational institutions should therefore strengthen teacher capability-building initiatives, instructional support systems, and inclusive educational policies to sustain holistic learner development in elementary education. Implications of the Study Schools should strengthen professional development programs focusing on holistic and inclusive instructional practices. Teachers may integrate more learner-centered and experiential learning activities to support holistic learner growth. Educational institutions should improve instructional resource allocation and stakeholder collaboration. Future studies may explore learners’ perspectives and quantitative assessments of holistic learner development outcomes. References Andres, A. (2019). Achievement Goals and Mathematics Achievement of the Senior High School Students. International Journal of English and Education, 8 (2). Andres, A. (2023). Establishing Quality Instrument for the Summative Assessment of Pre-Service Elementary Teachers. JETT. 14 (3), 9-16). Andres, A.D. (2022). Metacognition and Performance in Mathematical Problem-Solving Among Bachelor of Elementary (BEED) Pre-service Teachers. Central European Management Journal, 30 (4). 86-95. Antonio, A. (2021). Syntactical Scrutiny: Inaccuracies in the Lesson Planning of Non- Language Pre Service Teachers. International Journal of Arts, Sciences and Education, Balog, P., & Gonzales, E. (2021). From Linguistic Landscapes to Teaching Resources: A Case of Some Rural Areas in the Province of Quezon. International Journal of Arts, Sciences and Education, 1(2), 23–44. Banares, A. J. (2022). Reinterpreting Sonnet 18 by William Shakespeare through Stylistic Analysis. International Journal of Arts, Sciences and Education, 3(July Special Issue), 189–204. https://ijase.org/index.php/ijase/article/view/163. Bonoan, K. C., Bunagan, K. A., Calangi , A. D., Chan, E. P., Corpuz , L. P. ., Deseo, J. M. ., Suarez, R. H., Sumulong, B. I. ., & Flores, A. R. (2021). A Comparative Study on the Knowledge, Attitude, and Practices (KAP) on the Preventive Measures Against Covid-19 of the Residents in Rural (Lobo, Batangas) and Urban (Taguig City, Metro Manila) Areas in the Philippines . International Journal of Arts, Sciences and Education, 1(3), 77–123. Retrieved from https://ijase.org/index.php/ijase/article/view/35 Braun, V., & Clarke, V. (2006). Using thematic analysis in psychology. Qualitative Research in Psychology, 3(2), 77–101. Buncag, R. (2022). Parent-Assisted Modular Reading Program: Its Effect on Reading Performance During the Covid-19 Pandemic of Grade 5 Pupils of Biwag Elementary School, Tallag Cabagan Isabela. International Journal of Arts, Sciences and Education, 3(July Special Issue), 39–50. https://ijase.org/index.php/ijase/article/view/154 Caliboso, J., Bagalay, B., Santiago, M. Bayan, R., Aguinaldo, I., & Belo, J. (2025). Literary Texts as Cultural Tools: A Study on Contextualized Learning Strategies in Philippine Higher Education. International Journal on Culture, History, and Religion, 7(SI2), 340–355. https://doi.org/10.63931/ijchr.v7iSI2.205 Camiring-Picpican, H., Flores, K., Caban, R., Mohadali, S., Galdonez, D., & Alih, C. (2025). Pedagogical Innovations Based on Philippine Cultural Practices: A Framework for Culturally Responsive Teaching in Higher Education. International Journal on Culture, History, and Religion, 7(SI2), 433–451. https://doi.org/10.63931/ijchr.v7iSI2.168 Caranguian, C. B. (2022). Family-related Factors Influencing Success in the Licensure Examination for Teachers. International Journal of Educational Sciences. 38 (1-3), 62-69. Caranguian, C. B. (2023). Level of Parental Involvement as a Predictor of Academic Achievement and School Adjustment. Universidad de Granada.14(3), 138-143. CASEL. (2020). What is social and emotional learning? CASEL Official Website Florian, L., & Black-Hawkins, K. (2011). Exploring inclusive pedagogy. British Educational Research Journal, 37(5), 813–828. Gay, G. (2018). Culturally responsive teaching: Theory, research, and practice (3rd ed.). Teachers College Press Miller, J. P. (2019). The holistic curriculum (3rd ed.). University of Toronto Press Weimer, M. (2018). Learner-centered teaching: Five key changes to practice (2nd ed.). Jossey-Bass Official Website